Impact of Computer-Based Pedagogy on Pre-Service Teachers’ Academic Achievement in Ecology - Sheyin, Adejoke Olabisi; Omolara, Adu Deborah (NIU Journal of Humanities, 2018)
The experimental research investigated the effects of Computer-Based pedagogy on the achievement of pre-service teachers in an ecology group that was exposed to er-based instruction and the control group that received the conventional teaching Two hundred and thirty College of Education biology students (male and female) apled from the population of all students in two Nigerian Colleges of Education. After exposure to teaching, using computer-based instructional strategy and the aonal teaching method, as the experimental and control group respectively; pre-tests (-tests, using Achievement Test in Ecology (ATE) were conducted. Data collected analyzed using Analysis of Covariance (ANCOVA) to test the formulated hypotheses. The result showed a significant effect of treatment on the achievement of the students ((F(1,229)=138.255,p < .05). There was no significant effect of academic performance of the postacademic achievement scores (F (1,229) =.209). There was no significant >n effect of treatment and gender on students' academic achievement in ecology at the: level (F (I,229) = .234). The findings of this research have significant implications on practices, classroom practices, curriculum planning, and implementation in this era anon and communication technology. Keywords: Computer-Based Instruction, Science, Ecology, Achievement, Pre-service Teachers.